Examination of the Relationship Between Metabolic Syndrome and Obstructive Sleep Apnea in Iranian Patients with Type 2 Diabetes: A Case–Control Study - Sharifpour P (Dove Medical Press, 2020)
Pershang Sharifpour,1 Fazel Dehvan,2 Sahar Dalvand,3 Reza Ghanei Gheshlagh2 1Student Research Committee, Kurdistan University of Medical Sciences, Sanandaj, Iran; 2Clinical Care Research Center, Research Institute for Health Development, Kurdistan University of Medical Sciences, Sanandaj, Iran; 3Department of Epidemiology and Biostatistics, School of Public Health, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Reza Ghanei GheshlaghClinical Care Research Center, Research Institute for Health Development, Kurdistan University of Medical Sciences, Sanandaj, IranTel +98 9144050284Email rezaghanei30@gmail.comIntroduction: Obstructive sleep apnea (OSA) is a common risk factor for metabolic syndrome (MS) that increases the chance of cardiovascular disease, stroke, and mortality. Many studies have been conducted on this matter, but the results are still conflicting. The aim of the present study was to examine the relationship between metabolic syndrome (MS) and obstructive sleep apnea (OSA) in Iranian patients with type 2 diabetes (T2D).Patients and Methods: This matched case–control study was conducted with 190 patients with T2D in Sanandaj, Iran. The data were selected using the demographic questionnaire, clinical and anthropometric measures, the Berlin Questionnaire (BQ), and the National Cholesterol Education Program’s Adult Treatment Panel III (NCEP-ATP III). Participants were divided into two groups of high risk of OSA (experimental) and low risk of OSA (control). The data were analyzed using Stata, version 14.Results: The frequency of MS was higher in the OSA group than the control group (81.1% vs 70.5%), but the group difference was not statistically significant (p=0.127). The results of crude and age-sex adjusted logistic regression analysis revealed no significant association between OSA and the other variables under study (P> 0.05). Sensitivity analysis and external adjustment for BMI showed no significant relationship between OSA and the other variables under study (P=0.319).Conclusion: In the present study, no significant association was found between metabolic syndrome (MS) and obstructive sleep apnea (OSA) in patients with T2D; therefore, more studies should be conducted on this subject.Keywords: diabetes, sleep apnea, metabolic syndrome